Resolving Independent Dominating Set pada Graf Bunga, Graf Gear, dan Graf Bunga Matahari - Rafiantika Megahniah Prihandini; Nabilah Ayu Az-Zahra; Dafik; Antonius Cahya Prihandoko; Robiatul Adawiyah (Universitas Airlangga, 2023)
Resolving independent dominating set is the development of metric dimension and independent dominating set. Resolving independent dominating sets is a concept which discusses about determining the minimum vertex on a graph provided that the vertex that becomes the dominating set can dominate the surrounding vertex and there are no two adjacent vertices dominator and also meet the requirement of metric dimension where each vertex in graph G must have a different representation which respect to the resolving independent dominating set . In this study, we examined the resolving independent dominating set of flower graphs, gear graphs, and sunflower graphs.